A Passage of Nostalgia The Life and Work of Jacobus Kloppers - Viljoen, Martina (UJ Press, 2020)
Jacobus Kloppers, an eminent composer, organist, pedagogue, and scholar, significantly contributed to musicological and organ teaching in South Africa and Canada and, in the latter context, art music, and liturgical composition. A Passage of Nostalgia - The Life and Work of Jacobus Kloppers, as a symbolic gesture, constitute recognition of his work both in South Africa and Canada. This publication is unique in that, apart from relevant disciplinary perspectives, biographical and autobiographical narrative, and anecdote, all constitute a necessary means through which the authors illuminate Kloppers' compositional process and its creative outcomes. In this regard, Kloppers generously dedicated his time to the project to make information on his life and work available, often in complex ways. This retrospective input supports the work offered as an authentic, self-reflective recounting of a life of dedicated service in music. The construct of nostalgia as an overarching theme to this volume on some level denotes Kloppers' position of cultural and religious 'insidedness' and 'outsidedness'. However, apart from representing a return to a lost and challenging past, the composer's creative work affirms his individuality, sense of artistic self, and propensity for spiritual acceptance and tolerance. Moreover, nostalgia in his oeuvre takes on importance as a rhetorical artistic practice by which continuity is as central as discontinuity.